2021
DOI: 10.1093/ajcn/nqab295
|View full text |Cite
|
Sign up to set email alerts
|

Association of nut consumption with risk of total cancer and 5 specific cancers: evidence from 3 large prospective cohort studies

Abstract: Background The associations between nut consumption and cancer risk have not been extensively investigated. Objectives We aimed to examine the associations between nut consumption, especially specific types of nuts (peanut, tree nut, walnut, and tree nut other than walnut), and cancer risk. Methods Nut consumption was assessed by FFQ at baseline and updated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…The authors found an inverse association between total nut consumption and risk of ESCC in this cohort, although several study limitations were acknowledged, including the influence of preparation methods, an important factor that is not often considered [56]. A recent meta-analysis [57] of total nut, tree nut and peanut consumption and cancer incidence and mortality reported a 4% reduction in cancer mortality with higher nut intake, consistent with a recent meta-analysis by Zhang et al [58] However, other studies from the Giovannucci group [59,60] have shown limited efficacy of tree nut consumption and cancer risk. In a prospective study of nut consumption and risk of primary hepatocellular carcinoma (HCC), Sui et al [59] examined data collected in the NHS and HPFS and reported that nut consumption (walnuts and peanuts) was not strongly associated with HCC risk.…”
Section: Human Studiessupporting
confidence: 82%
See 2 more Smart Citations
“…The authors found an inverse association between total nut consumption and risk of ESCC in this cohort, although several study limitations were acknowledged, including the influence of preparation methods, an important factor that is not often considered [56]. A recent meta-analysis [57] of total nut, tree nut and peanut consumption and cancer incidence and mortality reported a 4% reduction in cancer mortality with higher nut intake, consistent with a recent meta-analysis by Zhang et al [58] However, other studies from the Giovannucci group [59,60] have shown limited efficacy of tree nut consumption and cancer risk. In a prospective study of nut consumption and risk of primary hepatocellular carcinoma (HCC), Sui et al [59] examined data collected in the NHS and HPFS and reported that nut consumption (walnuts and peanuts) was not strongly associated with HCC risk.…”
Section: Human Studiessupporting
confidence: 82%
“…In a prospective study of nut consumption and risk of primary hepatocellular carcinoma (HCC), Sui et al [59] examined data collected in the NHS and HPFS and reported that nut consumption (walnuts and peanuts) was not strongly associated with HCC risk. Additionally, Fang et al [60] analyzed data from the same prospective cohorts for health effects of various nuts, including walnuts. In contrast to earlier meta-analyses and case-control studies, no significant association was observed with the risk of total cancers, including lung, colorectal, bladder, breast, and prostate cancer [60].…”
Section: Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2023 meta-analysis that included only prospective studies reported an inverse association between total nut intake (highest vs. lowest) and the risk of cancers of the lung and stomach with pooled relative risks equal to 0.86 (CI: 0.81–0.91) and 0.79 (95% CI: 0.68–0.91), respectively [ 100 ]. The few cohort studies that investigated the association between nut consumption and total cancer incidence in cohorts from Europe and the USA with more than 20 years of follow-up and more than a total of 60,000 incident cancer events reported no clear association of 5+ times per week vs. never/or almost never consuming a serving of nuts [ 101 , 102 , 103 ].…”
Section: Tree Nuts Peanuts and Cancermentioning
confidence: 99%
“…The Netherlands Cohort Study No remarkable association [29] In vitro Inhibition of the proliferation of PCa cells [43] Cross-national study Inverse association [55] Population-based studies in Canada Remarkable inverse association [56] The Health Professionals Follow-up Study No significant association [57] Ecological study including 170 countries Inverse association [58] Greek population No significant association [59] Bladder cancer Patients newly diagnosed with bladder cancer Inverse association [60] Three large prospective cohort studies No significant association [61] Pancreas cancer The Nurses' Health Study Inverse association [11] The Netherlands Cohort Study A nonlinear dose-response relation [62] Population-based case-control study in the Netherlands No significant association [63] Colon cancer In vitro Inhibition of the survival of colon cancer cells [19] In vivo study on mice model Inhibition of nuclear factor kappa β signaling in intestinal epithelial cells [64] In vitro Significant decrease in the growth of colon cancer cells [65] In vivo study on mice model Suppression of colon carcinogenesis…”
Section: Prostate Cancermentioning
confidence: 99%